The Impact of Analytical Compliance on Sentence Structure in Texts - Nufa Visca Amaratya; Andika Danang Saputra; Putri Indah Lestari (International Forum of Researchers and Lecturers, 2024)
This research examines how adherence to analytical standards influences the structure of sentences within texts. By analyzing the relationship between analytical compliance and sentence construction, the study aims to uncover the effects of adherence to linguistic, syntactic, and contextual norms on text cohesion and readability. The findings shed light on the importance of analytical conformity in shaping sentence structures and enhancing overall text quality and comprehension.